EFFECT OF SOURCE OF NITROGEN, ITS LEVEL AND CROP DENSITY ON GROWTH AND YIELD OF LINSEED (Linum usitatissimum L.) - SUSANA BASAIAWMOIT; SHIKHA SINGH; NAPHISABET NONGPHLANG; POCHAMPALLY KAVYA; DHANANJAY TIWARI (The Bioscan, 2021)
A field experiment was conducted at the Crop Research Farm, Department of Agronomy, Naini Agricultural Institute, Sam Higginbottom University of Agriculture Technology and Sciences (SHUATS), Prayagraj (U.P.) in the years 2019–2020. The seeds of linseed cultivars (SHUATS Linseed-6) were sown at row spacing of 10, 20 and 30 cm. Three levels of different nitrogen along with two levels of FYM i.e.25 and 50 % were used. The objective was to study the effect of spacing and source of nitrogen on growth and yield of Linseed and to study the economics of all the treatment combination. Results revealed that higher plant height (86.46),plant dry weight (23.61), number of branches plant -1 (7.20), number of capsule plant -1 (42.13), number of seeds capsule -1 (7.47), 1000 grain weight (5.45), seed yield (1221.33kg/ha), stover yield (3111 kg ha -1 ) which was 23.19 % higher to that of treatment combination 100% Nitrogen through Urea + 10 x 5 cm. This was due to higher plant density, higher number of branches, and higher number of capsules per plant.